New Methods for the (Land)-Taking: Visualising the Narrative Networks of the Sturlubók Redaction of Landnámabók - Croci, Cassidy (2024)
This thesis combines conventional historical and literary methods with Social Network Analysis (SNA) and Visual Analytics (VA) to analyse the Sturlubók redaction of Landnámabók in an interdisciplinary way. This process facilitates the extraction of the approximately 3,100 individuals and their roughly 8,100 relationships in Sturlubók that when combined form the narrative networks (i.e. people and their relationships) of the text. These networks are then visualised and subjected to a large-scale visual and quantitative investigation to detect emerging social and geographical patterns, ultimately providing new insights into how the landnámsöld (c.870-930 CE) was remembered in the latter half of thirteenth century (c.1275-1280 CE). An introductory survey discusses the content, structure, and narrative tradition of Sturlubók and situates the thesis in Landnámabók scholarship (Chapter 1). In Chapter 2, the interdisciplinary methodological approach is outlined. Chapters 3 to 6 show how the application of SNA can shed new light on traditional approaches and interpretations can be revisited by applying SNA in various ways to Sturlubók. The narrative structure of Sturlubók is visualised to investigate how regional identities develop during and after the landnám (Chapter 3). Next, the question of whether Kolskeggr vitri’s influence can be detected in the narrative networks of Sturlubók is investigated (Chapter 4). Chapter 5 evaluates whether the different methods of land acquisition used by landnámsmenn influence their perceived importance in Sturlubók. Finally, Chapter 6, investigates how all 706 women collectively influence and operate in the narrative networks of Sturlubók. It is shown throughout the thesis that narrative networks of Sturlubók are complex. They emulate many features found in ‘small-world’ and ‘real-world’ social networks: this gives Sturlubók its characteristic texture of verisimilitude. These networks are multidimensional, multimodal, and diachronic, crafted and transformed over extensive periods resulting in a text localised to its time that fits paradigms of landnám collective memory. Ultimately, this thesis provides a new way to ‘read’ Sturlubók that creates new possibilities for further analysis on account of SNA and VA.